1983
DOI: 10.1111/j.1365-2621.1983.tb09151.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irradiation on the Inhibition of Clostridium botulinum Toxin Production and the Microbial Flora in Bacon

Abstract: The effect of irradiation (0.5, 1.0, 1.5 Mrad) on the microbiological safety and stability of temperature-abused (27"C, 60 days) bacon cured with, 1.5% NaCI, 0.25% sucrose, 0.3% NasP30ro, 0.055% Na-erythorbate, with or without NaN02 (40 p/g) was determined. Unioculated bacon (120 c(g NaNOz/g) had a sour odor within 13 days, and, if inoculated with ca. 2 C. botulinurn spores/g, 73% of the samples became toxic within 60 days. Irradiation with 0.5 Mrad prevented spoilage of uninoculated bacon by virtue of reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The level of 40 ppm NaN02 was also selected so that product safety would not be compromised. This concentration of NaN02 delayed swelling and toxicity in bacon inoculated with 2 spores/g of C. botulinum when compared to no-nitrite bacon (Rowley et al, 1983). These authors also obtained extensive data on bacon prepared with 40 ppm NaN02, uninoculated and inoculated (2 and 160 spores/g of C. botulinum), and irradiated with "Co in 0.5-Mrad absorbed dose increments from 0 to 1.5 Mrad.…”
Section: Methodsmentioning
confidence: 89%
“…The level of 40 ppm NaN02 was also selected so that product safety would not be compromised. This concentration of NaN02 delayed swelling and toxicity in bacon inoculated with 2 spores/g of C. botulinum when compared to no-nitrite bacon (Rowley et al, 1983). These authors also obtained extensive data on bacon prepared with 40 ppm NaN02, uninoculated and inoculated (2 and 160 spores/g of C. botulinum), and irradiated with "Co in 0.5-Mrad absorbed dose increments from 0 to 1.5 Mrad.…”
Section: Methodsmentioning
confidence: 89%
“…For example, irradiation causes a dose-dependent reduction in the quantities of sodium nitrite (NaNO 2 ) in meat products, subsequently, resulting in a loss of anti-botulinal activity [ 99 ]. However, as the irradiation does not completely eliminate the nitrite quantities, the anti-botulinal effects still persist for a long time [ 6 , 100 ]. For example, Barbut et al [ 94 ] reported that 40 mg/kg of sodium nitrite and 15 kGy sufficiently prevented toxin formation in C. botulinum (spores types A and B/g) inoculated bacon during two months of storage at 27 °C.…”
Section: Ionizing Radiations To Inactivate C Botulinummentioning
confidence: 99%
“…Because the organism of concern is, in this case, C. botulinum, whose endospores are extremely resistant to radiation, great care must be used in evaluating attempts to substitute irradiation for additives such as salt or nitrite in the preparation of processed meats. Unfortunately, several studies have indicated that irradiation of some processed meat products at doses of less than 10 kGy may not be beneficial and, in some cases, may result in decreased safety especially where there is an attempt to substitute the irradiation treatment for all or part of the nitrite or sodium chloride that would normally be used in such products (Anellis et al 1977a;Huhtanen et al 1986;Rowley et al 1983). However, the use of 2.5% NaCl together with 0, 5, or 10 kGy inhibited C. botulinum toxin formation in inoculated turkey frankfurters for 4, 30, and 40 days, respectively, when incubated at 27°C (Barbut et al 1987).…”
Section: Extension Of Shelf-life and Elimination Of Bacterial Pathogementioning
confidence: 99%